Proteome and secretome characterization of glioblastoma-derived neural stem cells - Okawa, Satoshi; Krijgsveld, Jeroen (Stem cells, 2017)
Glioblastoma multiforme (GBM) (grade IV astrocytoma) is the most common and aggressive primary brain tumor. GBM consists of heterogeneous cell types including a subset of stem cell-like cells thought to sustain tumor growth. These tumor-initiating glioblastoma multiforme-derived neural stem (GNS) cells as well as their genetically normal neural stem (NS) counterparts can be propagated in culture as relatively pure populations. Here, we perform quantitative proteomics to globally characterize and compare total proteome plus the secreted proteome (secretome) between GNS cells and NS cells. Proteins and pathways that distinguish malignant cancer (GNS) stem cells from their genetically normal counterparts (NS cells) might have value as new biomarkers or therapeutic targets. Our analysis identified and quantified ∼7,500 proteins in the proteome and ∼2,000 in the secretome, 447 and 138 of which were differentially expressed, respectively. Notable tumor-associated processes identified using gene set enrichment analysis included: extracellular matrix interactions, focal adhesion, cell motility, and cell signaling. We focused on differentially expressed surface proteins, and identified 26 that participate in ligand-receptor pairs that play a prominent role in tumorigenesis. Immunocytochemistry and immunoblotting confirmed that CD9, a recently identified marker of adult subventricular zone NS cells, was consistently enriched across a larger set of primary GNS cell lines. CD9 may, therefore, have value as a GNS-specific surface marker and a candidate therapeutic target. Altogether, these findings support the notion that increased cell-matrix and cell-cell adhesion molecules play a crucial role in promoting the tumor initiating and infiltrative properties of GNS cells.